Uganda : Technical Assistance Report-Report on the Prices Statistics Mission. (IMF Staff Country Reports; Country Report, 2017)
This Technical Assistance Report discusses technical advice and recommendations given by the IMF mission to the authorities of Uganda in relation to developing export and import price indices and rebasing the construction industry price index and hotels and restaurants producer price index. The survey methodology was determined covering the form design, selection of the sample of importers, conduct of the initialization interviews, and selection of samples of representative products for regular pricing. Detailed documentation was provided. A prototype of an Excel-based compilation system was prepared, which will form the basis for the development of an operational system of spreadsheets for the ongoing quarterly compilation of the import and export price indices.